2013
DOI: 10.2139/ssrn.2236208
|View full text |Cite
|
Sign up to set email alerts
|

Wages, Exchange Rates, and the Great Inflation Moderation: A Post-Keynesian View

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…It must be concluded that increased public wage bill in terms of GDP induces a decrease in exchange rate depreciation in Ghana and has a more significant long run negative effect. In the words of Keynes [29], Agénor and Hoffmaister [32], Mihaljek and Saxena [33], and Perry and Cline [6], inflation is the result of cost pressure emanating from wages. It must be reasoned from this that the negative impact of inflation on the value of the cedi influences the relationship between public wage bill and exchange rate depreciation in the long run.…”
Section: Long Run Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be concluded that increased public wage bill in terms of GDP induces a decrease in exchange rate depreciation in Ghana and has a more significant long run negative effect. In the words of Keynes [29], Agénor and Hoffmaister [32], Mihaljek and Saxena [33], and Perry and Cline [6], inflation is the result of cost pressure emanating from wages. It must be reasoned from this that the negative impact of inflation on the value of the cedi influences the relationship between public wage bill and exchange rate depreciation in the long run.…”
Section: Long Run Resultsmentioning
confidence: 99%
“…Drawing from Post-Keynesian and Structuralist inflation theories, the fall in inflation rate was primarily as a result of wage declines, fall in prices of products produced by international competition and impacts of the exchange rate [6]. Hence, inflation is the outcome of cost pressures coming from wages, prices of commodities, the real exchange rate and the resistance of wage to previous inflation.…”
mentioning
confidence: 99%
“…This basic equation is fundamental for our reasoning and to propose our equations describing what we call the low inflation regime. In the low inflation regime, the inflation rate is mainly due to conflicting claims between wage earners and capitalists over output (Perry and Cline, 2013); in other words, the conflict (and its resolution) between workers and capitalists over the distribution of revenue induces inflation dynamics and determines the distribution of income. In any case, it does not mean that inflation is exclusively due to the distribution conflict as we will explain later.…”
Section: Main Characteristicsmentioning
confidence: 99%
“…Hasil penelitian ini sesuai dengan studi yang dilakukan oleh Perry & Cline (2013), dan Afandi (2015), yang menyatakan bahwa harga BBM merupakan variabel utama dalam kegiatan produksi dan distribusi (cost-push inflation).…”
Section: Pengaruh Harga Bbm Terhadap Inflasi Inti DI Indonesiaunclassified